2002
DOI: 10.1002/clc.4960250405
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐induced platelet aggregation increases in patients with proximal and severe coronary artery stenosis

Abstract: SummaryBackground: Shear stress generated in stenosed arteries promotes platelet thrombi formation at the stenosed sites by accelerating the binding of von Willebrand factor (vWF) to platelets. Shear-induced platelet aggregation (SIPA) has been studied in acute coronary syndromes, but not in chronic coronary disease.Hypothesis: We investigated the effect of both the site and severity of coronary stenosis on SIPA in patients with chronic coronary artery disease.Methods: Shear-induced platelet aggregation was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…31 Our results support a direct relationship between stenosis severity, shear stress, and in situ platelet activation in human coronaries but show that atheroma burden per se, as measured by plaque volume, does not correlate with platelet activation in stable patients. This suggests that in stable coronary disease, shear stress is a more important determinant of platelet activation within coronary arteries rather than the amount of atheroma.…”
Section: Discussionsupporting
confidence: 58%
“…31 Our results support a direct relationship between stenosis severity, shear stress, and in situ platelet activation in human coronaries but show that atheroma burden per se, as measured by plaque volume, does not correlate with platelet activation in stable patients. This suggests that in stable coronary disease, shear stress is a more important determinant of platelet activation within coronary arteries rather than the amount of atheroma.…”
Section: Discussionsupporting
confidence: 58%
“…Shear-induced platelet aggregation is increased in chronic coronary artery disease (7,8) and myocardial infarction (7) and has been shown to be insensitive to aspirin (9) but sensitive to the combined therapy with aspirin and thienopyridine (7,10). We performed a prospective study of individuals (identified post hoc) with SAT to test the hypothesis that SIPA might identify differences between patients with or without SAT despite dual antiplatelet therapy.…”
mentioning
confidence: 99%
“…To clarify the different phenotypes of ISR with its thrombogenicity or thrombogenic tissue component is difficult by using such high-resolution devices as OCT because of no direct comparison for ISR lesions between histopathology and OCT appearance. The enhanced shear stress at a severe stenotic lesion activates platelets and invites an increasing risk of platelet aggregation in the native coronary artery [23][24][25]. High shear stress also has a vicious influence on the endothelial cell function preventing thrombus formation [26].…”
Section: Discussionmentioning
confidence: 99%